Obesity May Accelerate the Aging Process - Salvestrini, Valentina; Sell, Christian; Lorenzini, Antonello (Frontiers in Endocrinology, 2019)
Lines of evidence from several studies have shown that increases in life expectancy are now accompanied by increased disability rate. The expanded lifespan of the aging population impose a challenge on the continuous increase of chronic disease. The prevalence of overweight and obesity is increasing at an alarming rate in many parts of the world. Further to increasing the onset of metabolic imbalances, obesity leads to reduced life span and affects cellular and molecular processes in a fashion resembling aging. Nine key hallmarks of the aging process have been proposed. In this review, we will review these hallmarks and discuss pathophysiological changes that occur with obesity that are similar to or contribute to those that occur during aging. We present and discuss the idea that obesity, in addition to having disease-specific effects, may accelerate the rate of aging affecting all aspects of physiology and thus shortening life span and health span.